Repeat liver resection versus salvage liver transplant for recurrent hepatocellular carcinoma: A propensity score-adjusted and -matched comparison analysis. - Guo, Yuxin (The Korean Association of Hepato-Biliary-Pancreatic Surgery, 2023)
10.14701/ahbps.2019.23.4.305